2012
DOI: 10.1021/jp3005647
|View full text |Cite
|
Sign up to set email alerts
|

An Indium Tin Oxide Conductive Network for Flexible Electronics Produced Using a Cotton Template

Abstract: A regular indium tin oxide (ITO) conductive network is fabricated by a simple "dipping and drying" process using cotton as a template. The flexible composite consists of an interconnected conductive network of ITO, which acts as a transport channel for charge carriers, and a poly(dimethyl siloxane) substrate. The composite shows a very high electrical conductivity of ∼5 S m −1 , which is ∼12 times of magnitude higher than those of other ordinary ITO-based composites. Moreover, it exhibits superior electrical/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…[136][137][138][139] There is also much interest to look into the use of inkjet printers for fabricating ITO thin films, as inkjet printing potentially offers better cost-effectiveness, material savings, direct patterning, and printing efficiency as compared to current conventional fabrication techniques (for example, CVD, magnetron sputtering, and spin-coating). [136][137][138][139] There is also much interest to look into the use of inkjet printers for fabricating ITO thin films, as inkjet printing potentially offers better cost-effectiveness, material savings, direct patterning, and printing efficiency as compared to current conventional fabrication techniques (for example, CVD, magnetron sputtering, and spin-coating).…”
Section: Indium Tin Oxide Nanoparticle Inksmentioning
confidence: 99%
See 2 more Smart Citations
“…[136][137][138][139] There is also much interest to look into the use of inkjet printers for fabricating ITO thin films, as inkjet printing potentially offers better cost-effectiveness, material savings, direct patterning, and printing efficiency as compared to current conventional fabrication techniques (for example, CVD, magnetron sputtering, and spin-coating). [136][137][138][139] There is also much interest to look into the use of inkjet printers for fabricating ITO thin films, as inkjet printing potentially offers better cost-effectiveness, material savings, direct patterning, and printing efficiency as compared to current conventional fabrication techniques (for example, CVD, magnetron sputtering, and spin-coating).…”
Section: Indium Tin Oxide Nanoparticle Inksmentioning
confidence: 99%
“…[127] Metal oxides nanoparticle [131,132] • Thermal sintering not applicable [131,132] • 7.5-10.8 µΩ cm (Metalon ICI-002HV) [131] • 9 µΩ cm (Metalon ICI-002HV) [133] • 13-15 µΩ cm (Metalon ICI-003) [132] • 65-95 mΩ sq −1 (NS6130-10-1304) [130] • NovaCentrix [131,132] • Nanoshel [130] • Paquet et al [133] • Metalon ICI-002HV (16% CuO loading), Nova-Centrix [131] • Metalon ICI-003 (10% CuO loading), Nova-Centrix [132] • NS6130-10-1304, Nanoshel [130] Iron oxide nanoparticle inks • Not available • Good magnetic properties [134] • Low electrical conductivity [134] • Inductors • Radio frequency devices • Patch antennas [135] • Thermal drying [135] • Drying at 80 °C for 30 min [135] • Saturation magnetization of ≈12.4 under an applied field of 1 kOe [135] • Vaseem et al [135] • Not commercially available [136][137][138][139] • High sintering temperatures required for optimized transparency and electrical conductivity [127] Metal oxides nanoparticle [131,132] • Thermal sintering not applicable [131,132] • 7.5-10.8 µΩ cm (Metalon ICI-002HV) [131] • 9 µΩ cm (Metalon ICI-002HV) [133] • 13-15 µΩ cm (Metalon ICI-003) [132] • 65-95 mΩ sq −1 (NS6130-10-1304) [130] • NovaCentrix [131,132] • Nanoshel …”
Section: Bq321 - Screenmentioning
confidence: 99%
See 1 more Smart Citation
“…Although hybrid conductive cotton materials has been investigated directed in the area of wearable device (electronic textiles) 21,22 or used as pressure sensor,…”
Section: 20mentioning
confidence: 99%
“…The conductivity of the dried superhydrophobic fabrics was measured to be 37 Ω/cm. Hu et al [27] reported cotton fabric was dipped into the previously prepared ITO precursor solution (indium chloride and tin chloride) for 2 h under vacuum, dried at 60°C for 0.5 h and the same process was repeated three times. After calcination at 350-550°C for 4 h, the size of NTO particles over fabrics is changed to 20-30 nm resulting in conductive network.…”
Section: Nanoparticles Coatingmentioning
confidence: 99%